ANALYSIS OF FACTORS AFFECTING ROBUSTA COFFEE PRODUCTIVITY ON INCREASING FARMERS' ECONOMIC INCOME IN THE PERSPECTIVE OF ISLAMIC BUSINESS - Ahmad Sirojul Munir; Fatih Fuadi; Mia Selvina (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the influence of Robusta coffee productivity on the income of coffee farmers in Pekon Tambak Jaya, Way Tenong District, West Lampung, as well as to examine the implementation of Islamic business principles in their farming practices. The research employs a qualitative descriptive approach with 22 respondents selected purposively from a total population of 77 coffee farmers. Data collection was conducted through interviews, observations, and documentation, while data validity was ensured using method and source triangulation techniques. The findings indicate that fluctuations in Robusta coffee productivity are largely influenced by climatic conditions and farm management practices. Higher productivity generally leads to increased farmer income; however, farmers still face vulnerability due to unstable coffee selling prices. In addition, the study reveals that most farmers have implemented Islamic business ethics in their economic activities, including honesty in weighing products, transparency in determining prices, and the avoidance of interest-based financing. These practices reflect the application of ethical and fair principles in agricultural transactions within the local farming community. Keywords : Robusta Coffee; Farmer Income; Productivity; Islamic Business Ethics